Tinjauan Yuridis Pemidanaan Terhadap Pelaku Tindak Pidana Penjarahan - Komang Gede Reska Joanykernia Pradila; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Warmadewa Press, 2021)
The rapid development of the times in Indonesia in various aspects has made the behavior patterns of the Indonesian people diverse. Seen from a legal perspective, there is behavior that is in accordance with applicable norms and there is also behavior that deviates from applicable norms. One of the deviant acts is the crime of looting. Looting is the crime of theft which is carried out by forcibly taking other people's belongings which is carried out during natural disasters, riots, airplane accidents and train accidents. The purpose of this study is to analyze the criminal sanctions against the perpetrators of the crime of looting and the judge's considerations in imposing a sentence on the perpetrators of the crime of looting. This research applies normative research methods. The legal materials used are primary, secondary and tertiary legal materials with the technique of inventorying or tracing the relevant legal materials then classified or grouped and documented, recorded, quoted, summarized, reviewed as needed using a qualitative approach which is then analyzed systematically. The results of the study reveal that people who commit the crime of looting will be subject to criminal sanctions according to article 363 of the 2nd KUHP paragraph (1) by considering article 10 of the Criminal Code and it is obligatory for the perpetrators to be held accountable for their actions.